أثر الايمان بالملائكة في حياة الفرد والمجتمع - بالمهدي, سماح; اسحيمي, سعيدة; بن عيشة, ربيعة (جامعة الوادي university of eloued, 2018)
This study dealt with the impact of faith in angels in the life of the individual and society according to the analytical descriptive approach, which included what faith in the angels leaves of the behavioral and moral reflection in the life of the believer peace be upon them. In this study we discussed a number of definitions included in the title, What is stated in the revelation of the news of the angels that we must believe in them, and we mentioned at the end of this study to mention some aspects of faith in the angels and follow them.
عقيدة